Strengthening governance for sustainable silvopastoral restoration and enhanced livelihood - Louhaichi, Mounir; Hassan, Sawsan (International Center for Agricultural Research in the Dry Areas, 2023)
Silvopastoral systems in dry areas play a crucial role in enhancing land productivity and resilience, offering environmental benefits, and positively influencing the livelihoods of communities. Sabihia Site, managed by the Forestry Department, serves as a pilot site, shedding light on the challenges and successes of implementing silvopastoral systems. As a demonstrative model for sustainable practices, this site showcases favorable outcomes, including soil and water conservation, reduced livestock feeding costs, and enhanced biodiversity. The establishment of a governed Community-Based Organization (CBO), specifically the Groupement de Développement Agricole (GDA), emerges as a key factor for success. The two workshops conducted in June and July 2023 explore the legal and procedural intricacies of forming the GDA, underscoring the importance of community participation and participatory governance. Involving diverse stakeholders, including government entities, local communities, and NGOs, the workshops aim to raise awareness among the local community about the legal steps involved in formulating the silvopastoral GDA. The sessions outline a roadmap for GDA formation, fostering collaboration, facilitating knowledge transfer, and promoting sustainable development. Key recommendations emanating from these workshops encompass the development of a comprehensive program for optimal pasture utilization, the establishment of the GDA, implementation of specialized training courses, support for local silvopastoral species, and the promotion of continual collaboration among institutions. The workshops underscore the significance of evidence-based decision-making, scientific research, and participatory governance as integral components for ensuring the enduring success of silvopastoral systems in the dry areas of Tunisia.